Coronavirus disease 2019 pandemic: Strengthening health sector response amidst the background of global economic crisis - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The Coronavirus Disease-2019 (COVID-19) pandemic should be looked upon as much more than a public health emergency, as it has significantly impacted the global economy. Owing to the fact that the disease spreads by close contact, many of the nations imposed social restrictions, with an aim to reduce the spread of the disease. However, the bitter truth is that such measures enormously affects the income opportunities of individuals & families, and the financial status of the community and the nation at large. During these difficult times, each nation should start their response by funding all the components of the emergency response plan, strengthen the foundations of the health system and remove the possibility of financial constraints, which can prevent people to access health care. In conclusion, the COVID-19 pandemic has made us to come to a scenario where we have to not only save lives, but even ensure that livelihoods of people are sustained. Thus, the need of the hour is to strengthen the health sector through financial assistance, and simultaneously plan for the release of the lockdown to try to bring our economy back on track.